Electrospun ZnO Nanofiber Membranes for Photocatalytic Water Treatment: A Comparative Review of Fabrication Strategies - Aditya Rianjanu; Eka Nurfani; Tarmizi Taher (Green and Sustainable Materials Society, 2026)
Electrospun ZnO nanofiber membranes are promising candidates for photocatalytic water treatment, offering directional charge transport, high surface-to-volume ratio, and self-standing membrane architectures that enable straightforward catalyst retrieval and reuse, a critical advantage over dispersed semiconductor nanoparticle systems where post-treatment recovery remains a major bottleneck. However, the fabrication route fundamentally determines membrane morphology, mechanical integrity, retrievability, and photocatalytic performance. This review classifies electrospinning-based fabrication into three routes: the Ceramic Membrane Route (precursor/polymer blending followed by calcination), the Hierarchical Membrane Route (secondary ZnO growth on electrospun polymer scaffolds), and the Composite Membrane Route (direct electrospinning of pre-synthesized ZnO/polymer dispersions). The Ceramic Membrane Route yields high-crystallinity membranes with up to 100% pollutant degradation but poor mechanical integrity that hinders membrane retrieval. The Composite Membrane Route provides single-step fabrication with the best demonstrated reusability (10 cycles at 97–99% retention), 200-fold lower zinc leaching, and excellent mechanical robustness for repeated retrieval and deployment, positioning it as one of the more operationally mature options for near-term deployment. The Hierarchical Membrane Route delivers the highest surface area, the fastest degradation kinetics, and uniquely combines photocatalysis with membrane filtration in a single device, making it a particularly promising long-term direction once its multi-step processing is streamlined and continuous-flow scale-up is realized. This comparative framework guides the selection of fabrication strategy based on membrane retrievability, performance, and development-stage requirements.